Analisis Pasal 43 Undang-Undang Pengadilan Hak Asasi Manusia dalam Kasus Penghilangan Orang secara Paksa Tahun 1997/1998 - Satya Kumarajati (Lentera Hukum, 2018)
This paper examines problems as the result of the absence of statement on the establishment of Human Rights Ad hoc Court in the Human Rights Court Act Number 26 Year 2000. By highlingting the kidnapping of activists in the final days of New Order regime in 1997-1998, as Article 43 of Human Rights Court Act, the power to adjudicate is attached to the Human Rights Court. However, the absence of explicit provisions to the establishment of teh Ad hoc Court of Human Rights whether before or after the preliminary investigation to be made by the Indonesian Commission on Human Rights (Komnas HAM), Attorney General argues that no subsequent measures on the results of the investigation made by Komnas HAM into the process of investigation due to the Ad hoc Court of Human Rights was not established. The aim of this paper is to provide views on the establishment of the Ad hoc Court of Human Rights by using doctrinal research with statute and case approaces. As this paper shows, it concludes that the Ad hoc Court of Human Rights was established after premilinary investigation and full investigation as proposed by the House of Representatives which is assigned throug Presidential Resolution. Keywords: Ad hoc Court of Human Rights, Preliminary Investigation, Investigation